Quality of the Healthy Work Environment and Retention Intention among Nurses in Tertiary Hospitals: Mediating Roles of Need Satisfaction and Work-Life Balance - Da-Young Lee; Hyeon-Young Kim (Journal of Fundamental Nursing Science, 2026)
Purpose: This study examined whether need satisfaction and work-life balance mediated the relationship between the quality of the healthy work environment and retention intention among nurses in tertiary hospitals. Methods: Data were collected from 187 nurses with at least one year of clinical experience in tertiary hospitals between March 27 and April 19, 2025. Participants completed a structured self-report questionnaire distributed through online communities. Data were analyzed using IBM SPSS Statistics 26.0, and mediation effects were tested with PROCESS Macro Model 4. Results: The quality of the healthy work environment significantly predicted need satisfaction (β=.43, p